Chronotope and Territoriality: A Proposal to Approach Power Relations in Latin American Audiovisual Representations - Rosana Mauro (Conexión, 2023)
This article proposes the relationship between the concepts of chronotope, by the Russian theorist Bakhtin, and territoriality (from a decolonial perspective) to analyze Latin American audiovisual fiction, focusing on power relations. These reveal themselves discursively, among other ways, in spatio-temporal clues that, in turn, dialogue with extradiegetic social contexts. In urban representations, we highlight the tension between public and private, while in natural environments there is a tension between nature (merged with the man represented by the native inhabitants) and civilization (represented by the colonizing white man).